LIGHT EXPOSURE’S EFFECTS ON INACTIVE STATE DURATION AND SLEEP LATENCY IN ZEBRAFISH (DANIO RERIO) LARVAE INSOMNIA MODEL - Zamroni Afif; Mochammad Istiadjid Eddy Santoso; Husnul Khotimah; Irawan Satriotomo; Edi Widjajanto; Masruroh Rahayu; Shahdevi Nandar Kurniawan; Dheka Sapti Iskandar; Annisatul Hakimah; Syafiatul Azizah; Nurvia Andriani; Kartika Agustina (Malang Neurology Journal, 2022)
Background: Insomnia is defined as difficulty falling or staying asleep or a sleep state that cannot restore the body's condition. The zebrafish (Danio rerio) is a vertebrate model that has been extensively studied to study sleep and neurological disorders. One of the most widely used methods to examine the effect of the light-dark cycle on the circadian system is by exposing animals and humans to pulse wave light.